A conquista do povo: notícias populares e a oposição ao governo João Goulart - Cestari, Larissa Raele (2013)
This dissertation analyzes the political opposition movement against João Goulart‟s administration (1961 - 1964), led by the Paulista liberal elite, simultaneously involving business segments and political leaders affiliated to the União Democrátic a Nacional (UDN). To understand such movement, I chose to examine the newspaper Notícias Populares , founded in 1963 by the national president of UDN, the Paulista entrepreneur Herbert Levy, as part of his strategy against Goulart. The newspaper aimed at re aders from the urban popular classes in São Paulo. The goal of this dissertation is to understand the role played by Notícias Populares in the political struggle of the period, which implies also the analysis of the perception of the popular classes by the sector represented by Levy in the beginning of the 1960s.